1995
DOI: 10.1177/112067219500500208
|View full text |Cite
|
Sign up to set email alerts
|

Management of Posterior Segment Foreign Bodies and Long-Term Results

Abstract: The management of 158 posterior segment intraocular foreign bodies (IOFB) was retrospectively analyzed: transscleral magnet extraction via the pars plana was used for 40 magnetic IOFB, transscleral extraction via the IOFB bed for 35 magnetic and 4 non-magnetic IOFB, pars plana vitrectomy (PPV) for 44 magnetic and 32 non-magnetic IOFB, and open-sky vitrectomy for 3 non-magnetic IOFB. Final visual acuity of 0.02 and better was achieved in 104 out of 119 magnetic IOFB (87%) and 24 out of 39 non-magnetic IOFB (62%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
2
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 13 publications
3
6
2
1
Order By: Relevance
“…In agreement with previous reports (Heimann et al 1983;Karel & Diblik 1995), our results showed that RD was a crucial factor for poor visual outcome after IOFB injuries. Two multivariate analyses (Hutton & Fuller 1984;Brinton et al 1982) demonstrated that eyes with RD had a worse prognosis in severe ocular trauma.…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with previous reports (Heimann et al 1983;Karel & Diblik 1995), our results showed that RD was a crucial factor for poor visual outcome after IOFB injuries. Two multivariate analyses (Hutton & Fuller 1984;Brinton et al 1982) demonstrated that eyes with RD had a worse prognosis in severe ocular trauma.…”
Section: Discussionsupporting
confidence: 94%
“…Other authors reported 8%–17% after magnetic extraction 311 29 30Two multivariate analyses 17 26 demonstrated that retinal detachment had a poorer prognosis in severe ocular trauma. Percival 24 noted 22% of eyes with postoperative retinal detachment and found four essential risk factors: intravitreous haemorrhage (odds ratio (OR) 8.4), foreign body size over 1 mm 3 (OR 4.5), transvitreous manipulation (OR 1.8), and vitreous loss (OR 1.7).…”
Section: Discussionmentioning
confidence: 99%
“…Závažnost tohoto typu poranění spočívá především v riziku rozvoje infekční komplikace, toxické reakce na cizí těleso a rozsahu oční léze v průběhu nitrooční trajektorie cizího tělesa [16]. Jako negativní prognostické faktory byly definovány: velikost nitroočního tělesa větší než 5 mm 2 , přítomnost relativního aferentního pupilárního defektu (RAPD), prolaps nitroočních tkání, přítomnost odchlípení sítnice nebo krvácení do sklivce při vstupním vyšetření a vstupní zraková ostrost horší než 0,1 [8,14,16].…”
Section: Diskuseunclassified